Die verhouding tussen Klassieke retoriek en epistolografie - E. Cornelius (Literator, 1994)
The objective of this article is to determine the relationship between Classical rhetoric and epistolography. Both epistolographical and rhetorical studies of letters are found among scholars. Some scholars prefer to work only epistolographically and others only rhetorically. The problem arises when some scholars try to combine these two perspectives, resulting in an approach in which the body of the letter is studied rhetorically and the letter opening and closing epistolographically. As an aid to determine the relationship between these two disciplines, a short summary of the theoretical frameworks of each is given and the Classical textbooks on both disciplines are studied. Once the relationship has been made dear, the article is concluded by proposing rhetoric as the framework for the interpretation of the communicative function of letters and epistolography as the framework for the interpretation of the form of letters.